2020
DOI: 10.1002/hec.4108
|View full text |Cite
|
Sign up to set email alerts
|

The impact of drug quality ratings from health technology assessments on the adoption of new drugs by physicians in Germany

Abstract: Payers are increasingly calling for the value of new drugs to be measured explicitly. We analyze how the availability of drug quality ratings by health technology assessment (HTA) agencies affects the adoption of new drugs by physicians in Germany. We combine data from drug quality ratings, promotional spending, and a physician panel. In a latent utility model, time to adoption is specified as a function of quality rating, promotional spending by manufacturers, and physician‐specific variables. As expected, dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…On the other hand, lower prices mean that a health care system will save money in the long run, potentially allowing for spending in other areas that could lead to a gain in life years or other beneficial outcomes for society. Also, prior research has shown that a positive HTA evaluation may be seen by physicians as a positive rating of a pharmaceutical’s quality from a trusted third-party source, thereby increasing the speed with which the pharmaceutical is diffused [ 42 ]. This faster diffusion could at least partly compensate for the effects of a delayed launch.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, lower prices mean that a health care system will save money in the long run, potentially allowing for spending in other areas that could lead to a gain in life years or other beneficial outcomes for society. Also, prior research has shown that a positive HTA evaluation may be seen by physicians as a positive rating of a pharmaceutical’s quality from a trusted third-party source, thereby increasing the speed with which the pharmaceutical is diffused [ 42 ]. This faster diffusion could at least partly compensate for the effects of a delayed launch.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings allow for the calculation of the commercial value of clinical studies, which has clear implications for practice. Lastly, Blankart and Stargardt (2020) and Olson and Yin (2021) focus on the effects of valence. The former find that public evidence reporting positive results accelerates initial drug adoption, whereas the latter conclude that public evidence reporting negative or mixed effects for children lowers the drug prescriptions to them.…”
Section: Scientific Evidence Effectsmentioning
confidence: 99%
“…Studies from other countries indicate that a positive HTA evaluation from a trusted third party source increased the speed of pharmaceutical adoption. 40 …”
Section: Lessons From China’s Experiencementioning
confidence: 99%